Nonlinear elliptic inequalities with gradient terms on the Heisenberg group. (July 2015) - Bordoni, Sara; Filippucci, Roberta; Pucci, Patrizia
Abstract: In this paper we give sufficient conditions both for existence and for nonexistence of nontrivial nonnegative entire solutions of nonlinear elliptic inequalities with gradient terms on the Heisenberg group. The picture is completed with the presentation of a uniqueness result which is, as far as we know, the first attempt for general equations with gradient terms on the Heisenberg group.